Incompatibility classes and fruit set in natural populations of arctic bramble (Rubus arcticus L.) in Finland - Tammisola, Jussi (Agricultural and Food Science, 1988)
In Finnish natural populations, arctic bramble proved uniformly self-incompatible. In vigorous and richly flowering populations, the intensity of fruit set is governed by the number of incompatibility classes present. Most non-fruiting populations contain only one incompatibility class (and most likely only one clone) and therefore totally lack compatible pollen. Richly fruiting populations usually contain at least three incompatibility classes. A clone with an estimated size of 80 metres and age of 160 years was found. This supports the vegetative burst explanation for the “sudden appearance” of arctic bramble populations. For the purposes of plant breeding, a large genetic collection is required. In cultivation, a thorough mixture of at least three varieties is recommended. The study was dynamically optimized. A computerized guidance system was constructed, which analyzed the accumulating results and yielded recommendations for forthcoming crosses. For the analysis into equivalence classes of incompatibility, a stepwise clustering algorithm of the single move type, based on the maximum likelihood principle, was introduced. This partitioning was based on the number of seeds in a cross, considering it as a stochastic variable. Seed number probability distributions in intraclass and interclass pollinations were acquired utilizing non-parametric density estimation. Finally, both incompatibility class and seed probability estimates were adjusted together iteratively. A recommendation algorithm was produced, based on a partially heuristic principle of maximum lability maximum stability. With the aid of the guidance system, incompatibility classes could be resolved using about one tenth of the number of crosses required in a conventional system.